2020
DOI: 10.1002/cplu.202000312
|View full text |Cite
|
Sign up to set email alerts
|

Urchin‐Like Cobalt‐Copper (Hydr)oxides as an Efficient Water Oxidation Electrocatalyst

Abstract: The development of efficient and low‐cost oxygen evolution reaction (OER) catalysts is essential for the generation of clean hydrogen energy from water splitting. Herein, a novel hierarchical urchin‐like cobalt‐copper (hydr)oxide in situ grown on copper foam (CoCuOxHy(S)/CF) was synthesized through the electrochemical transformation of cobalt‐copper sulfides (Co9S8‐Cu1.81S) via anodization process. This CoCuOxHy(S)/CF anode exhibited a low overpotential (η) of 274 mV at a current density of 100 mA cm−2 with a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Here, they demonstrated that the synergistic effect between the core and the shell and the strong electron exchange through sulphur to both the metals is responsible for superior electrocatalysis, which eventually resulted in the improvement of the electrocatalytic activity. 184 In order to validate the superiority of Cuf as an electrode active material, Liu et al theoretically studied the role of Cuf in their as-developed samples, CoS x and Cu@CoS x using DFT calculations to analyse the role of Cuf by taking the (111) facet of Co 9 S 8 , which has the lowest surface energy to absorb water molecules, preferably over the facet. As shown in Fig.…”
Section: Multifunctional Applications Of Cuf For Clean Energy Technol...mentioning
confidence: 99%
“…Here, they demonstrated that the synergistic effect between the core and the shell and the strong electron exchange through sulphur to both the metals is responsible for superior electrocatalysis, which eventually resulted in the improvement of the electrocatalytic activity. 184 In order to validate the superiority of Cuf as an electrode active material, Liu et al theoretically studied the role of Cuf in their as-developed samples, CoS x and Cu@CoS x using DFT calculations to analyse the role of Cuf by taking the (111) facet of Co 9 S 8 , which has the lowest surface energy to absorb water molecules, preferably over the facet. As shown in Fig.…”
Section: Multifunctional Applications Of Cuf For Clean Energy Technol...mentioning
confidence: 99%
“…Hydrolysis of copper from the molecular complex often under high applied potentials [46] as well as surface leaching of the metal‐chalcogenides and nitrides, phosphides resulted in formation of highly active copper oxide and/or copper hydroxides [39] . In situ formed and/or the copper oxides nanostructure prepared independently [47] remain effective materials for OER [48] …”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…Iron is the most abundant metal element in the earth’s crust and exhibits several interesting characteristics in OER. For instance, pure Fe (oxy)­hydroxides are much less active than Ni or Co (oxy)­hydroxides in OER. However, when Fe is employed as substituting cocatalyst into Ni or Co (oxy)­hydroxides, the OER activity can be dramatically enhanced by ∼100-fold. ,,, This indicates that chemical environments around Fe is crucial for OER. In this regard, Fe-based single-atom catalysts (SACs), e.g., Fe–N–C SACs with FeN 4 coordination structures, have been widely reported as promising catalysts for OER and oxygen reduction reaction (ORR) because of the suitable binding strength for intermediates. Sulfur-treated MOF-based Fe–O–S SACs were also reported to exhibit excellent OER performance. , All these studies lead to the conjecture that incorporation of single-atom (SA) level distribution of Fe atoms with nonmetal atoms is responsible for the high catalytic performance of Fe-based SACs. ,, Benzenehexathiol (BHT), as a class of planar thiolate-based MOFs, aroused our interest because of its outstanding electric conductivity and high density of MS 4 moieties. In the present work, nanocrystals of an iron coordination polymer, iron-benzenehexathiol (Fe-BHT), is selected as a model catalyst to demonstrate the cascading of thermocatalysis and electrolysis for OER.…”
mentioning
confidence: 99%